Assessment of Self-Adhesive Resin Composites: Nondestructive Imaging of Resin–Dentin Interfacial Adaptation and Shear Bond Strength. (December 2015) - Makishi, Patricia; Pacheco, Rafael R.; Sadr, Alireza; Shimada, Yasushi; Sumi, Yasunori; Tagami, Junji; Giannini, Marcelo
Abstract: Shear bond strength (SBS) and the interfacial adaptation (IA) of self-adhesive resin (SAR) composites to dentin were evaluated. Two SARs [Vertise Flow (VTF) and Fusio Liquid Dentin (FLD)] were evaluated and compared with a conventional restorative system [adhesive: OptiBond FL and composite: Herculite Précis (OBF/HP)]. Human third molars were used for SBS testing and IA imaging ( n =7) using optical coherence tomography (OCT). Flattened dentin disks were prepared and the composites were applied into molds (2.4 mm diameter) that were positioned on dentin. Samples were subjected to SBS testing and OCT analysis, which considered an increase in signal intensity at the bonded interface as evidence of internal gaps. SBS data were analyzed by one-way analysis of variance and Tukey's test and IA data (% distribution of high brightness values) by Kruskal–Wallis and Dunn's test ( p ≤0.05). No statistically significant difference in SBS was observed between VTF (13.9±3.6 MPa) and FLD (11.3±3.2 MPa), whereas OBF/HP showed higher average strength (27.3±6.1 MPa). However, there was a statistically significant difference in IA when VTF (33.3%) was compared with FLD (1.2%) and OBF/HP (1.5%). The conventional restorative system exhibited superior SBS performance compared with SARs. However, the IA of FLD to dentin had values that were not significantly different from OBF/HP.